An Analysis of Psychological Distress Profiles and their Correlates in Interdisciplinary Health-care Professional Students - Samantha Mladen MS; Ashlee Loughan PhD; Patricia Kinser PhD; MaryKate Crawford; Anna Jones BA; Sarah Edwards BS; Bruce Rybarczyk PhD; Sarah E Braun MS (SAGE Publishing, 2019)
Background Health-care professional (HCP) students experience high levels of burnout, characterized by work- and school-related stress. Burnout is associated with a host of negative psychological and health outcomes. It may also contribute to cognitive dysfunction and decreased work productivity and may be related to trait mindfulness. This study cross-sectionally explored psychological distress and its correlates in a sample of interdisciplinary HCP students using cluster analysis. Method Fifty-seven interdisciplinary HCP students completed validated measures of burnout, depressive and anxiety symptoms, perceived stress, and rumination, which were entered into a cluster analysis. A neuropsychological test measured executive function; validated questionnaires assessed work productivity and trait mindfulness. Relationships between cluster membership and classroom productivity, executive function, and trait mindfulness were investigated. Results Burnout, depressive symptoms, and perceived stress were reported at high rates in this sample. The cluster analysis yielded 4 clusters, categorized as follows: Healthy, Ruminative Healthy, Moderate Distress, and High Distress. Cluster membership significantly differed based on trait mindfulness and classroom productivity. Trait mindfulness was related to classroom productivity. Although not significant, there were small to medium associations between executive function and both cluster membership and trait mindfulness. Discussion Cluster membership was highly related to trait mindfulness and classroom productivity, suggesting these are important correlates of psychological distress in HCP students. Taken together, these results underscore the need for interventions, especially ones that are mindfulness-based, to manage stress and work-relevant functioning in HCP students.